Field quantifications of probability of detection and search patterns to form protocols for the use of detector dogs for eradication assessments. Issue 6 (5th June 2022) - Hoffmann, Benjamin D.; Faulkner, Craig; Brewington, Laura; Lawton, Faye
Abstract: The use of detector dogs within environmental programs has increased greatly over the past few decades, yet their search methods are not standardized, and variation in dog performance remains not well quantified or understood. There is much science to be done to improve the general utility of detector dogs, especially for invertebrate surveys. We report research for detector dog work conducted as part of yellow crazy ant eradication. One dog was first used to quantify the probability of detection (POD) within a strictly controlled trial. We then investigated the search patterns of two dogs when worked through sites using different transect spacings. Specifically, we quantified their presence within set distances of all locations in each assessment area, as well as the time they took to assess each area. In a GIS, we then calculated the relative percentage of the entire search area within six distance categories, and combined this information with the POD values to obtain a site‐level POD. The calculated relationship between distance and POD was extremely strong ( R 2 = 0.998), with POD being 86% at 2 m and 28% at 25 m. For site‐level assessments conducted by the two dogs, both dogs achieved the highest site‐level POD when operated on the lowest transect spacing (15 m), with POD decreasing significantly as transect spacing increased. Both dogs had strong linear relationships between area assessed and time, with the area assessed being greater when the transects had greater spacing. The working style of the two dogs also resulted in significantly different assessment outcomes. In 1 h one dog could assess approximately 9.2 ha with transects spaced 20 m apart, and 6.8 ha with transects spaced 15 m apart, whereas the second dog could only assess approximately 6.9 ha with transects spaced 20 m apart, and 4.9 ha with transects spaced 15 m apart. Our study provides insight into the ability of dogs to detect yellow crazy ants, and sets the basis for further science and protocol development for ant detection. With the lessons learned from this work, we then detail protocols for using detector dogs for ant eradication assessments. Abstract : Our study quantifies the ability of dogs to detect yellow crazy ants, further quantifies site‐level probabilities of detection for eradication determinations, and highlights the basis for further science and protocol development for ant detection.